Comparative Analysis of the Poverty Landscape of Nepal - Gautam, Sahadev; Aryal, Ananta; Thapa, Kusum (Nepalese Journal of Society and Culture, 2025)
This study presents Nepal’s poverty landscape using data from the four rounds of the Nepal Living Standards Survey (NLSS I–IV), covering the period from 1995/96 to 2022/23. While Nepal has achieved a notable decline in national poverty headcount rates (from around 42 percent in NLSS I to approximately 20 percent in NLSS IV), this progress remains uneven and fragile. The findings highlight that poverty reduction has been heavily reliant on temporary income sources such as remittances and seasonal work, rather than on sustainable domestic employment or structural transformation. Deep disparities persist across geography, caste, gender and wealth, especially affecting rural and remote regions. Intra-poor inequality is identified as a critical concern, with some poor households experiencing far deeper deprivation than others. The study also compares methodological variations across the four NLSS rounds, showing how changing definitions and survey techniques influence poverty measurement. Ultimately, fi ve key dimensions (Reliance on remittance, Stagnation on Agriculture, Structural inequalities, Vulnerability to shocks) are discussed as enduring causes of poverty in Nepal.